STRATEGI PENGATURAN DIRI DALAM BELAJAR SEBAGAI MEDIATOR HARAPAN ORANG TUA DAN MOTIVASI INTRINSIK TERHADAP PRESTASI AKADEMIK - Novita, Leni; Latifah, Melly (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2014)
Some factors had been found to explain its effect on student achievement both internal and external factors of students. The comprehensive study that explains these two factors in giving effect jointly to academic achievement is still limited. This study examined the effects of child and family characteristics, parent’s expectation, intrinsic motivation, and self-regulated learning strategies on academic achievement of junior high school. The samples of this study were selected by random sampling. One hundred and forty nine of junior high school students in Bogor, 8th grade, were selectedas samples in this study. This study found that parents expectation were positively affecting intrinsic motivation and intrinsic motivation were positively affecting selfregulated learning strategies. Self-regulated learning strategies were positively affecting academic achievement. Self-regulated learning strategies were found as mediator for the effect of parent’s expectation and intrinsic motivation towards academic achievement. Therefore, parents and teachers should be able to raise the intrinsic motivation of students so that students can perform self-regulated learning strategies that can improve their academic achievement.